Employment status and job-studies relevance of social science graduates: The experience from a Greek public university - Aglaia G. Kalamatianou; Foteini Kougioumoutzaki (International Journal of Economic Sciences and Applied Research, 2012)
Research on social science graduates' employment prospects reaches contradictor conclusions intensifying the scepticism on the value of these disciplines in the labour market. The paper examines two important labour market outcomes of these graduates, employment status and job-studies relevance taking into account gender and time of graduation. This is put into the Greek context, then examined further in a case study on graduates of a public University that exclusively serves social sciences. Results indicate deterioration of the graduates' employment opportunities, lower employment status of female graduates, and persistence of a high degree of job-studies no relevance over time.
Keywords: I23; J20; 330; social sciences graduates; employment; job-studies relevance; Greece; Absolventen; Sozialwissenschaft; Berufseinstieg; Beschäftigung; Griechenland